In vivo kinematics of the ACL-deficient limb during running and cutting. - Waite, J; Beard, D; Dodd, C; Murray, D; Gill, H (2005)
Anterior cruciate ligament-deficient (ACLD) knee kinematics during high-demand activities are poorly understood. We have devised a new method, using gait analysis, to more accurately assess 3-D in vivo kinematics of the knee. This has enabled us to report on how knee kinematics are altered after ACL rupture, during running and cutting. Fifteen unilaterally ACLD subjects were assessed using a 12-camera 100 Hz VICON motion analysis system. Simultaneous electromyographical (EMG) recordings were used to assess the role of the sensorimotor system in knee joint stability. All subjects were able to perform demanding cutting activities without experiencing symptoms of instability. We found that running produces fundamentally different kinematic patterns to those seen during walking. Tibiofemoral translation in the anteroposterior plane is controlled to within normal limits. Conversely, coronal translation and rotation are poorly controlled. We found that the injured leg was maintained in greater extension during the stance phase of all running activities studied and that the quadriceps muscle was active for longer during this period. We believe that low-demand activities, such as walking, do not reproduce kinematics relevant to ACLD instability and that future investigations into functional instability in the ACLD knee should focus on coronal and rotational displacements.